Name Shapes Identity through Linguistic Landscape of Kampung Bugis Banten Province - Perdana, Purnama Rika; Fitriani, Dini; Handayani, Reli (IJLECR (International Journal of Language Education and Cultural Review), 2024)
Name shapes identity. A name, especially an ethnic name, can be seen as the unit of linguistics that contains meaning. From a linguistics perspective, the analysis of a name is not only about the language used on a name. It may reveal much information such as people's migration, history, or genealogy. As one of the oldest settlements in Serang, the name of Kampung Bugis, which is located on the coast side of Banten, proved the old migration path of the people from the past. The name Kampung Bugis draws the identity of the residents or the people who once lived in that area. The name straightforward refers to a certain group of people from Makassar, South Sulawesi. Besides, there are 13 villages in Kampung Bugis which represent the existence of the Bugis people from the ancestor to the descendant. Until now, the location of Kampung Bugis can be found in Kasemen district and the name of it lasts for several decades. However, what makes the name last longer? This research explores factors that made the name of Kampung Bugis exist for a hundred years in Banten. Furthermore, this research also wants to explore the toponymic pattern of every place name that surrounds Kampung Bugis. Data in this research is the name of villages near Kampung Bugis in Kasemen district collected from the Banten Governoor website and sorted into several categories. Data is analyzed by using toponymy theories. The result shows that the names of every village near Kampung Bugis represent the existence of the Buginese of Makassar around Banten since many years ago. It proves that the mobility of an ethnic group can be tracked through a place name. Besides, the traditional activities of an ethnic group can be a distinctive factor that helps a place name last for years.